As relações entre profissionais da educação: a afetividade na educação infantil - Santos, Rafaele Paulazini Majela dos (2019)
The questions which has guided this research are: How does teachers notice the affectivity? How does affectivity appear in the relationships between education professionals in the Centro de Educação Infantil (CEI)? This paper aim to identify how affectivity emerge from relationships between education professionals at a public CEI, located in the City of São Paulo, Brazil. The goals are: To understand what teachers know about affectivity and to illustrate how affectivity can be identified in CEI’s teachers and pedagogical coordinator daily routine. Five teachers and one coordinator from a CEI has guided this research that was realized in the first half of 2017 and completed in the second half of 2018.This is a qualitative research and the data gathering was made by following different CEI’s environments and by conducting semi-structured interviews with the CEI’s teachers and the pedagogical coordinator. This study was based on the following theoretical references: Paulo Freire (in order to explain the affectivity study), Moysés Kuhlmann Jr, Sônia Kramer, Zilma de Oliveira and Ana Bruel (to explain the early childhood education). The results has shown that affectivity is barely recognized on the relationships between the teachers and coordinator at the study case CEI, which reflects on the CEI’s teamwork development. According to the teachers interviewed, Pedagogical Coordination is a support for all the CEI’s development job and that is why they emphasises the importance of the professional in such role. Who should dialogue with the teaching group and the different ideas in the articulation of an educational project. For this, they believe that listening, looking and perceiving the other is part of their attribution. Likewise, the interviewed coordinator are value relationship qualification to construct an enjoyable work environment that encourage mutual respect, speaking, desires and feelings expressions, as well as rights for everyone. Such environment make clear that all the aforesaid elements composes the affectivity. The teachers has shown that the affectivity is crucial on the relationship between teachers and the pedagogical coordinator to report conflicts, great and bad times they live or lived in their daily routine at CEI.